Mediating Confessions in Central Europe: The Ecumenical Activity of Valerian Magni, 1586–1661 - Louthan, Howard (The journal of ecclesiastical history, 2004)
The Capuchin friar, Valerian Magni, was one of the most influential churchmen of the first half of the seventeenth century. A confidant of Pope Urban VIII, an advisor to the emperor Ferdinand II and an intimate of the Polish king Władysław IV, Magni worked tirelessly as a religious mediator for nearly fifty years. This article investigates his ecumenical activity in two major arenas, Bohemia and the Polish-Lithuanian Commonwealth. In the Czech kingdom Magni collaborated with young Archbishop Harrach to counter the Jesuits' harsher policies of reCatholicisation while in Poland he endeavoured to reunite both Protestant and Orthodox communities with the Catholic Church.